Controllable Cetrimide – Assisted Hydrothermal Synthesis of MoFe2O4 and Coupling with Al2O3 as an Effective Photocatalyst for Decolorization of Indigo Carmine Dye - Mohammed Ali Hameed; Luma Majeed Ahmed (Indonesian Journal of Chemistry, 2024)
This research focuses on the MoFe2O4 nanoparticles synthesized via the hydrothermal method in the presence of positive surfactant- Cetrimide (CT) as a template and stabilizer. This is vital to prevent the agglomeration and reducing its activity. The mean crystal sizes of MoFe2O4 and its composite with alumina system were observed to be 23.97 and 47.41 nm, respectively. The shapes of MoFe2O4 and its composite are nanoplate and like-popcorn nanoparticles. The EDX spectra demonstrated that the MoFe2O4 and its composite are truly synthesized with high purity. The FTIR proved the MoFe2O4 is normal spinel. Based on the Tauc equation, band gaps were measured and found to be 2.78 and 4.05 eV for MoFe2O4 and its nanocomposite. The photo decolorization efficiency (PDE) of indigo carmine dye (IC) using MoFe2O4 nanoparticles and its nanocomposite was discovered to be 90.84 and 91.50%, respectively, at pH 5.3, 10 °C for 50 min. This photoreaction obeys the pseudo-first order, exothermic, spontaneous, and negative activation energy, that attitude to the multi-step occurs in chain reactions. This behavior depends on the speed of the binding step of the dye with Fe3+, Mo6+, or Al3+ in the crystal lattice of MoFe2O4 nanoparticle and its nanocomposite.